Evaluating the Validity and Reliability of Competency Instruments for Tuberculosis Nurses in Primary Health Centers of Bondowoso District - Wardani, Hamidah Retno; Wulandary, Rany Agustin; Riskika, Siti (Journal of Health Science and Prevention, 2024)
A strategy is needed to tackle the problem of tuberculosis in Indonesia. Both in terms of infrastructure, funding, policy and human resources (HR). One of the most needed of the four components is human resources. The availability of human resources plays a major role in the success of TB elimination. In achieving this, an instrument is needed that can be used as a guideline in improving the quality of human resources. The research method used in this study is research and development using Aiken's V analysis to measure content validity, and reliability analysis using Cronbach's Alpha test and Kappa test. The results obtained that 96 indicators described from RCN have a very high validity category of 23 indicators, high validity of 68 indicators, and moderate validity of 5 indicators, with reliable items (0.667) but with very poor inter-rater agreement of <0.000. Therefore, the tuberculosis nurse competency guidelines derived from the Royal College Nursing have good validity and reliability to be tested as an instrument for assessing the competence of tuberculosis nurses at the Puskesmas in Bondowoso Regency.